Hubungan Coping Stress dengan Motivasi Belajar Mahasiswa Prodi BK pada Mata Kuliah Statistika - Nurul Azmi Saragih; Dwi Novita Sari (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
This study aims to find out there is a stress coping relationship with the motivation to learn guidance and counseling students in statistical subjects. The data collection instrument used to measure stress coping and learning motivation is the Likert scale. Coping stress is measured based on the forms of emotional focused coping stress and problem focused coping, on learning motivation measured based on the types of learning motivation that is intrinsic and extrinsic. The population of this study was guidance and counseling students and the sample of this study were 57 people. The data analysis used is Simple Correlation. The results showed that stress coping had a correlation with learning motivation with a calculated r value of 0.680> r table 0.261. In this analysis r count is positive, the relationship between the two variables is directly proportional, namely the increasing stress coping will increase student learning motivation in statistical subjects, on the contrary the decrease in stress coping will decrease students' learning motivation in the statistics course.